(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
Each year, some hundreds of teachers (all levels and all disciplines) propose to the National Center for Educational Innovation and Experimentation their new digital products to facilitate the learning of their discipline with their students. Mathematics teachers regularly participate in this event. In this article, we evaluated the mathematics teachers participation in this contest during the first seven editions of the competition (2005-2011). We concluded that mathematics teachers are the most prized, especially those working in primary schools. We finished our article by the recommendation proposals for better success this experience in future editions.